ENGLISH BENEFIT FOR FOOD AND BEVERAGE SERVICE EMPLOYEES AT OPI INDAH HOTEL PALEMBANG - Sari, Novita; Iryanti, Nurlista; Fitri, Hidayatul (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
ABSTRACT The research is about English benefit for food and beverage service employees at OPI Indah Hotel Palembang. English is an international language, as an employee of food and beverage service, we need to know English to get benefit in servicing. The point of the research is English benefit for food and beverage service employees at OPI Indah Hotel Palembang. The purpose of this research is to know the benefit of English for food and beverage service employees at OPI Indah Hotel Palembang. The researchers used a descriptive qualitative method because there in the form of words written or spoken from the sources and observed behavior and is not intended to test hypotheses or testing the relationship among variables. In conclusion, success of hotel operations is depend on staff quality. Finally the researchers found the result and conclusion that gave a very much benefit for the writers themselves and the readers. OPI Indah Hotel Palembang should be always upgrading English skill for food and beverage service employees. Penelitian ini tentang manfaat bahasa Inggris bagi karyawan layanan makanan dan minuman di OPI Indah Hotel Palembang. Bahasa Inggris merupakan bahasa internasional, sebagai pegawai food and baverage service kita perlu mengetahui bahasa inggris untuk mendapatkan keuntungan dalam pelayanan. Inti dari penelitian ini adalah manfaat Bahasa Inggris bagi karyawan food and baverage service di OPI Indah Hotel Palembang. Tujuan dari penelitian ini adalah untuk mengetahui manfaat bahasa Inggris bagi karyawan food and baverage service di OPI Indah Hotel Palembang. Penulis menggunakan metode deskriptif kualitatif karena berupa kata-kata tertulis atau lisan dari sumber dan perilaku yang diamati dan tidak dimaksudkan untuk menguji hipotesis atau menguji hubungan antar variabel. Kesimpulannya, keberhasilan operasional hotel bergantung pada kualitas staf. Akhirnya penulis menemukan hasil dan kesimpulan yang memberikan manfaat yang sangat besar bagi penulis sendiri dan pembaca. OPI Indah Hotel Palembang hendaknya selalu meningkatkan kemampuan bahasa Inggris bagi karyawan dalam layanan makanan dan minuman.